Uji Toksisitas Ekstrak Cacing Tambelo (Bactronophorus thoracites) dengan Metode Brine Shrimp Lethality Test : Toxicity Test of Wood-boring Shipworm (Bactronophorus thoracites) using Brine Shrimp Lethality Test - Okmawaty Anwar, Lely; Fatmah Sari, Sri; Ambo Elo, Asrul; Rosmawati, Rosmawati; Nurdiyanty Nurdin, Iin; Said, Anwar (Jurnal Pengolahan Hasil Perikanan Indonesia, 2021)
Shipworm, local name tambelo, is an organism that live on dead Rhizophora sp timbres. The objective of this research was to determine the toxicity of shipworm extract using brine shrimp lethality test. Shipworm were collected from mangrove forests of Moolo Village, Batukara Subdistrict, Muna District, in Southeast Sulawesi. Extract of shipworm was prepared using methanol solvent. Toxicity test by brine shrimp lethality test was done through two stages of testing, preliminary and definitive test. Preliminary test was aimed to determine the range of lethal concentration (LC50), this range was used in the next definitive test. The preliminary test used a concentration of 10, 100, 1,000; and 0 μg.ml-1 as control. The definitive test used 4 concentrations in triplicates, 17,78, 31,61, 56,21, 99,94, and 0 μg.ml-1 as control. Data obtained from definitive test were subjected to probic analysis. The analysis showed that LC50-24hours of tambelo extract was equal to 42,431 μg.ml-1. LC50 value indicated that the toxicity of shipworm was very toxic to brine shrimp.